2020
DOI: 10.1002/pld3.289
|View full text |Cite
|
Sign up to set email alerts
|

The commitment of barley microspores into embryogenesis correlates with miRNA‐directed regulation of members of the SPL, GRF and HD‐ZIPIII transcription factor families

Abstract: Microspore embryogenesis is a model for developmental plasticity and cell fate decisions. To investigate the role of miRNAs in this development, we sequenced sRNAs and the degradome of barley microspores collected prior to (day 0) and after (days 2 and 5) the application of a stress treatment known to induce embryogenesis. Microspores isolated at these timepoints were uniform in both appearance and in their complements of sRNAs. We detected 68 miRNAs in microspores. The abundance of 51 of these miRNAs differed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Up-regulation of GSTF2 during the first stages of ME in different species has been described 9 , 12 , 26 . Its role is probably related to cell protection against the harmful effects of ROS generation, enhancement of microspores viability and reprogramming efficiency 31 , 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up-regulation of GSTF2 during the first stages of ME in different species has been described 9 , 12 , 26 . Its role is probably related to cell protection against the harmful effects of ROS generation, enhancement of microspores viability and reprogramming efficiency 31 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Reprogramming of the microspore and initiation of embryogenesis involve genome-wide changes of gene expression that allow the cell fate program to be halted and switched to a new developmental pathway 8 . Recently harnessed advanced methods of wide transcriptome analysis allowed the selection of differentially expressed genes during ME initiation and ELS development 9 12 . Majority of them has been identified as being involved in cell protection against stress, sugar metabolism, signaling and proteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bélanger et al (2020) investigated the role of miRNA for developmental plasticity and cell fate reprogramming within the barley microspore. Their findings indicated that the switch toward embryo differentiation involved miRNA-directed regulation of members of the ARF, SPL, GRF, and HD-ZIPIII transcription factor families.…”
Section: Applications For Gametophyte Reprogrammingmentioning
confidence: 99%
“…Some of them appear due to stress responses. Furthermore, miRNA-directed regulation of several transcription factor families (ARF, SPL, GRF, and HD-ZIPIII) was needed for the transition of microspores toward the embryogenesis pathway [ 207 ]. Differential expression of small RNAs was also denoted in the early development of broccoli ( Brassica oleracea var.…”
Section: Introductionmentioning
confidence: 99%